2010
DOI: 10.1080/10286020.2010.485566
|View full text |Cite
|
Sign up to set email alerts
|

Three new lupane-type triterpenes from Ceriops tagal

Abstract: Three new lupane-type triterpenes, 3 alpha-O-trans-feruloylbetulinic acid (1), 3 alpha-O-trans-coumaroylbetulinic acid (2) and 3beta-O-cis-feruloylbetulin (3), together with 10 known triterpenes (4-13), were isolated from the aerial parts of the mangrove plant Ceriops tagal. The structures of the three new compounds were established by means of spectroscopic data analyses and chemical methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In addition, it is reported that the crude extract of the plant possesses the activities to cure for hepatitis and diabetes [10]. Previous chemical investigation revealed that C. tagal not only abounded in tannins and triterpenoids [11,12], but also contained diverse dolabrane-type diterpenes such as tagalsin A-U [13][14][15] and tetraterpens [16,17]. Terpenoids from the root of C. tagal possess antifouling activity, while dolabrane derivatives exerted antifeedant and anticancer activities.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is reported that the crude extract of the plant possesses the activities to cure for hepatitis and diabetes [10]. Previous chemical investigation revealed that C. tagal not only abounded in tannins and triterpenoids [11,12], but also contained diverse dolabrane-type diterpenes such as tagalsin A-U [13][14][15] and tetraterpens [16,17]. Terpenoids from the root of C. tagal possess antifouling activity, while dolabrane derivatives exerted antifeedant and anticancer activities.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the full relative configuration of compound 1, 28-norolean-2,3β-dihydroxy-14,17-diene-16-one, was established as shown (Figure 1). Compounds 24 were identified as β-amyrin (2) [3d], 3α-O-transcoumaroylbetulinicacid (3) [7], and 3-acetylaleuritolic acid (4) [8] by comparison of their NMR and MS data with those in the previous literatures. All isolated compounds were evaluated for their cytotoxic activity against the cell lines of A549 and A2058.…”
mentioning
confidence: 99%
“…Moreover, five known compounds (2-6) were obtained from the leaves of T. wilfordii and identified as p-coumaroylkaempferol (2), 14 tripteryol B (3), 15 3β-O-transcoumaroylbetulinic acid (4), 16 camaldulenic acid (5) 17 and crategolic acid (6) 18 based on the NMR data and comparison with literature data (Figure 2).…”
Section: Structural Elucidationmentioning
confidence: 99%